1998
DOI: 10.1001/archotol.124.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Role of Soluble Adhesion Molecules During Immunotherapy for Perennial Allergic Rhinitis

Abstract: Decrease in serum sICAM-1 levels during immunotherapy is probably involved in the working mechanisms of immunotherapy, but modulation of serum sVCAM-1 levels is not likely related to the clinical effect of immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Secrist et al [15] demonstrated that production of IFN-g by allergen-specific CD4 þ T cells was not affected in grass pollen and mite allergic subjects on immunotherapy whereas IL-4 production was reduced by immunotherapy and that the levels of IL-4 produced are inversely related to the length of time on immunotherapy. We demonstrated previously that serum levels of IL-4 in patients with perennial allergic rhinitis were decreased by immunotherapy [23,39]. In our previous serological study for patients with seasonal allergic rhinitis, pollen immunotherapy reduced a seasonal activation of Th2 response and additionally switched the seasonal preferential activation of Th2 cells to reciprocal activation of Th1 cells with treatment over several years [14].…”
Section: Discussionmentioning
confidence: 84%
“…Secrist et al [15] demonstrated that production of IFN-g by allergen-specific CD4 þ T cells was not affected in grass pollen and mite allergic subjects on immunotherapy whereas IL-4 production was reduced by immunotherapy and that the levels of IL-4 produced are inversely related to the length of time on immunotherapy. We demonstrated previously that serum levels of IL-4 in patients with perennial allergic rhinitis were decreased by immunotherapy [23,39]. In our previous serological study for patients with seasonal allergic rhinitis, pollen immunotherapy reduced a seasonal activation of Th2 response and additionally switched the seasonal preferential activation of Th2 cells to reciprocal activation of Th1 cells with treatment over several years [14].…”
Section: Discussionmentioning
confidence: 84%
“…Ohashi et al. (23) reported that the percentage decrease in sICAM‐1 concentration was significantly correlated with the duration of immunotherapy and with the percentage of the decrease in symptom scores in allergic rhinitis. Our data further demonstrated lower expression of CD54 and CD69 after immunotherapy in asthmatic children with a good response.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the method used in this study have been described elsewhere. 2,[6][7][8] In brief, all the patients were asked to complete daily symptom diary cards for 14 days before we assessed their nasal symptom scores. The daily symptom cards included the number of sneezing attacks and nose blows, and the degree of nasal obstruction.…”
Section: Clinical Assessment Of Symptom Scoresmentioning
confidence: 99%
“…The details and the justification of each method used in the present study have been described elsewhere. [6][7][8]12,13 The minimum sensitivity of each assay was 40 U/mL of soluble IL-2R, 40 ng/mL of soluble ICAM-1 and soluble VCAM-1, and 0.75 pg/mL of IL-4.…”
Section: Scoring Of Nasal Obstructionmentioning
confidence: 99%
See 1 more Smart Citation